On translativity of absolute Rogosinski-Bernstein summability methods - Azmi K. Al-Madi (International Journal of Mathematics and Mathematical Sciences)
The paper is concerned with the problem of translativity of an absolute Rogosinski-Bernstein summability methods (Bh); 0≦h≦1. The paper contains two results that when h; 12≦h≦1, |Bh| is translative and when h; (0<h<12), then |Bh| is not translative neither to the left nor to the right.